Reverie and reality : poetry on travel by late imperial Chinese women - Wang, Yanning, 1976- (Lexington Books, 2014)
Reverie and Reality investigates late imperial Chinese gentry women's poems on travel ranging from the seventeenth century to the early twentieth century. These poems written by groups of women after they "stepped out of the inner quarters" display their diverse journeys, profound experiences of social life, and earnest sentiments. Their travel and poems on travel can be considered milestones in the histories of women's life and literature.